Parâmetros toxicológicos em carpas (Cyprinus carpio) expostos a uma formulação comercial de clomazone (gamit®) - Cattaneo, Roberta (2011)
Commercial formulations of the herbicide clomazone have been widely used in agriculture and fish farming to control weeds. Fish can be affected when the water reaches the drainage waterways, causing an imbalance in the aquatic ecosystem. In order to evaluate a possible contamination, we determined LC50 (96h) using a commercial formulation containing clomazone (Gamit®). We verified the metabolic, enzymatic, and genotoxic parameters as well as the oxidative stress in juvenile carp (Cyprinus carpio). Firstly, in order to determine the LC50 for the acute toxicity test, , the animals were exposed to the concentrations of 10, 20, 30, 40 and 50 mg/L of clomazone for 96 h and the fish behavior was analyzed during this period. After exposure, we verified the activity of the enzyme acetylcholinesterase (AChE) in muscle and brain of the dead fish and the live carp. Secondly, fish were exposed to the herbicide for 7 days, both in field (rice crop) and laboratory conditions. The concentration used in the rice crop and the laboratory was 0.5 mg/L. After the experimental period of 7 days under laboratory conditions and 7, 30, and 90 days under rice crop conditions, brain, liver and muscle of fish were sampled to carry out the toxicological analysis. The parameters studied were enzymatic activity of AChE, catalase (CAT) and glutathione S-tranferase (GST) in different tissues of this species. Some markers of oxidative stress, such as protein carbonylation and thiobarbituric acid reactive substances (TBARS) levels in liver tissue were also analyzed. Some metabolic parameters such as glucose, glycogen, lactate, protein, and ammonia as well as amino acids in liver and muscle of carp were also measured. In plasma, we measured glucose, lactate, and protein. Thirdly, carp were exposed to approximately 15% of the LC50 (5.0 mg/L) for 7 days. We verified the formation of reactive oxygen species (ROS) and micronucleus, and the comet test was performed in order to investigate the presence of DNA damage. In the first study we observed that fish exposed to 20, 30, 40 and 50 mg/L showed behavioral changes and LC50 (96h) was 30.35 mg/L. In addition, it was found that the activity of the enzyme AChE showed no significant changes in the brain of the fish that died at the concentrations tested (30, 40 and 50 mg/L), and the muscle of dead fish had an increase in this enzyme when they were exposed to 50 mg/L of clomazone. The activity decreased significantly in the brain AChE of fish that remained alive after 96 h of exposure to 10, 20 and 30 mg/L, but increased in the muscle of the surviving fish exposed to all concentrations tested. In the second experiment results showed that fish exposed to 7 days had no changes in AChE under field conditions. However, a decrease in the activity of this enzyme in muscle was observed under laboratory conditions. During the same period of exposition, the parameters of oxidative stress conditions changed both under the field and in laboratory conditions. However, metabolic parameters were altered only under field conditions. After 30 and 90 days, AChE activity did not change under field conditions. Disturbances in oxidative stress parameters and metabolism in different tissues were evident in the tissues up to 90 days after treatment. The results showed that the activity of AChE changed only under laboratory conditions, and that oxidative stress associated with metabolic parameters can be good indicators of contamination for clomazone in C. Carpio in rice field conditions. In the third experiment, the results showed an increased formation of ROS and a significant micronucleus (MN) and DNA damage in erythrocytes after exposure to 5.0 mg/L of the herbicide clomazone. Given these results, we can conclude that the herbicide studied can be dangerous to Cyprinus carpio when exposed to it due to increased ROS, which in turn cause oxidative stress evidenced by changes in enzyme markers, metabolic, genotoxic and oxidative stress. However, further studies are needed in order to verify the safety of this herbicide is when associating rice and fish.